PERIOPERATIVE MANAGEMENT OF ANTICOAGULANT AND ANTIPLATELET THERAPY IN ELECTIVE NEUROSURGERY PATIENTS: A NARRATIVE REVIEW - Dr Umair Aftab Baig; Dr Ayesha Zahid; Dr Muddassir Anis; Dr Zainab Bashir; Dr Rao Moiz Mansoor; Dr Syed Lareb Ali Shah; Dr Amber Shams (Journal of Population Therapeutics and Clinical Pharmacology, 2025)
Perioperative management is difficult in patients scheduled for elective cranial or spinal neurosurgery, as many patients are on chronic anticoagulation or antiplatelet therapy, which may increase the risk of bleeding complications. This article describes a risk-stratified perioperative approach to antithrombotic therapy. Important considerations include the indication for anticoagulation (e.g., atrial fibrillation, mechanical valves, recent stents), thrombotic risk scores (CHA₂DS₂-VASc, Caprini) and bleeding risk of the procedure. Warfarin is usually stopped 5 days before surgery, and reversal is performed using vitamin K and 4F-PCC in emergencies. DOACs are to be withheld 24-72 hours pre-op based on renal function and bleeding risk and with the availability of specific reversal agents idarucizumab, andexanet alfa. Anticoagulants, antiplatelet agents, including aspirin and P2Y₁₂ inhibitors, are managed dependent on surgical timing and stent history, and bridging is only indicated rarely. The guidelines recommend against routine bridging for anticoagulants and recommend individualized care. The report also associates an active antifibrinolysis with a favourable clinical outcome.16 Agreement within the neurosurgical community is for a longer preoperative hold period with antiplatelets because the likelihood of a hemorrhagic complication is greater in crossover patients than in those undergoing neurosurgical procedures. This structured approach, based on available evidence and expert opinion, is designed to maximise risk avoidance and benefit in the neurosurgical patient.